PAVING STONE BERBAHAN ABU SAMPAH TANAMAN - Wahyudi, Yusuf (INERSIA lnformasi dan Ekspose Hasil Riset Teknik Sipil dan Arsitektur, 2016)
Abstract This paper discusses about the advantage of organic disposal ash as an additive on paving stone mixture. The organic disposals such as leaves, wood stick, etc. were taken from garbage tank at the market, living area, and temporary tank. Then they were burnt in to an artificial furnace at temperature of 28-500°C for about 195 minutes. The mix design were 1 portland cement: 3 sand: 3 stone ash: organic ash of 0%, 10%, 11%, 12%, 13%, 14% and 15% of cement weight: 0,6 water. The result showed that organic disposal ash ratio was 0.05, and the gradation was observed in zone III. The weight of paving stone containing organic disposal ash was smaller than normally paving stone. The more organic disposal ash the lighter weight of paving stone. The compressive strength of paving stone containing 12% of plant ash was the strongest, it was 119% of the control. Key word: compressive strength, paving stone, organic disposal ash